Prognostic factors of melanoma patients with satellite or in-transit metastasis at the time of stage III diagnosis. - Benjamin Weide (PLoS ONE, 2013)
BACKGROUND: Prognosis of patients with loco-regional skin metastases has not been analyzed in detail and the presence or absence of concurrent lymph node metastasis represents the only established prognostic factor thus far. Most studies were limited to patients already presenting with skin lesions at the time of initial diagnosis. We aimed to analyze the impact of a broad penal of prognostic factors in patients with skin metastases at the time of first metastatic spread, including patients with synchronous lesions already present at the time of initial diagnosis, stage I/II patients with loco-regional recurrence and patients initially presenting with skin metastasis but unknown primary melanoma. PATIENTS AND METHODS: We investigated disease-specific survival of 380 patients treated at our department between 1996 and 2010 using Kaplan Meier survival probabilities and Cox-proportional hazard analysis. RESULTS: Five-year survival probability was 60.1% for patients with skin metastases only and 36.3% for those with synchronous nodal metastases. The number of involved nodes and a tumor thickness of at least 3 mm had independent negative impact on prognosis. A strong relationship was identified between the risk of death and the number of involved nodes. Neither ulceration nor the timing of the first occurrence of metastases as either in stage I/II patients, at the time of excision of the primary melanoma or initially in patients with unknown primary tumor, had additional effects on survival. CONCLUSION: Lymph node involvement was confirmed as the most important prognostic factor for melanoma patients with loco-regional skin metastasis including those with unknown primary tumor and stage I/II patients with skin recurrence. Consideration of the tumor thickness and of the number of involved lymph nodes instead of the exclusive differentiation into presence vs. absence of nodal disease may allow a more accurate prediction of prognosis for patients with satellite or in-transit metastases.